Monochorionic twins with 15q26.3 duplication presenting with selective intrauterine growth restriction and discordant cardiac anomalies: A case report. Issue 8 (6th July 2022) - Kannan, Suraj; Bodurtha, Joann N.; Hamosh, Ada; Jordan, Christopher
Abstract: Background: Duplication of the distal end of chromosome 15q has been previously implicated in a characteristic overgrowth syndrome. Additionally, many patients have other congenital malformations, including cardiac, renal, genital, and musculoskeletal anomalies. However, some patients may present with intrauterine growth restriction and short stature. Different breakpoints within 15q, as well as different environmental factors, may underlie these varied presentations. Case Presentation: We discuss monochorionic‐diamniotic twins with a ~345 kb maternally inherited duplication in 15q26.3. The twins presented with discordant pathology—one twin with a single umbilical artery, selective intrauterine growth restriction, and multiple cardiac defects including aortic coarctation, aortic valve stenosis, and ventricular septal defect, whereas the other twin was unaffected. To our knowledge, this case represents the smallest reported duplication of distal 15q. Conclusion: The discordant phenotype seen in the twins is likely due to a complex interplay between genetic and environmental causes. The affected infant presented prenatally with growth restriction and a single umbilical artery rather than overgrowth, potentially due to a unique breakpoint within 15q. This, in turn, may have produced hemodynamic perturbations between the twins, leading to discordant cardiac disease. Our report thus highlights the importance of genetic and nongenetic mechanisms underlying discordant anomalies in monochorionic twins. Abstract : We discuss monochorionic‐diamniotic twins with a ~345 kb maternally inherited duplication in 15q26.3. The twins presented with discordant pathology ‐ one twin with single umbilical artery, selective intrauterine growth restriction, and multiple cardiac defects including aortic coarctation, aortic valve stenosis, and ventricular septal defect, while the other twin was unaffected. To our knowledge, this case represents the smallest reported duplication of distal 15q.